INVESTIGATIONS AND DIAGNOSIS OF GIANT PERIURETHRAL CONDYLOMA AND EFFICACY OF THE MANAGEMENT WITH CONVENTIONAL APPROACH: A CASE REPORT - Ariwicaksono, Stefanus Cahyo; Mirza, Hendy (Indonesian Urological Association, 2022)
Objective: This study aims to show our first case of female with periurethral condyloma and how we managed it. Case(s) Presentation: A 40-year-old female came with asymptomatic lesion in the genital area for 4 months, without any history of promiscuity. The physical examination showed a mass of 5 x 5 cm located in the periurethral area. The patient underwent mass excisions without any complication, further pathological examination confirmed the diagnosis of CA. Discussion: After operation and discharge there are no sign of recurrence after 6 months follow up. Conclusion: Despite the rare occurrence in periurethral region, clinicians should be aware of CA case in female and for our first case we used mass excision with satisfactory result.